AKTIVITAS ANTIOKSIDAN DAN KUALITAS KEFIR DENGAN IMBANGAN SUSU KAMBING DAN SARI BERAS HITAM YANG BERBEDA - , YUDHIANTI PRATIWI; , Dr. Ir. Nurliyani, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Black rice has active components that are beneficial for the health of anthocyanins which act as antioxidants to counteract free radicals. Goat milk contains complete nutritional components and has better digestibility than dairy milk. The purpose of this study was to determine the antioxidant activity and quality of kefir with different balance of goat milk and black rice extract. There are five balance between goat milk and black rice extract, which is 100:0